(untitled) (Journal of Applied Learning and Teaching, 2024)
Simulation has become a well-integrated modality of learning in pre- and postgraduate healthcare education programmes. The use of advanced technologies and the delivery of complex simulation-based learning opportunities require adequate preparation of healthcare educators. This paper details a European collaborative development and utilisation of an educational framework designed to prepare educators for the delivery of simulation-based learning strategies. The framework was subsequently adapted by a commercial partner and an evaluative study identified the impact of this programme of education on United Kingdom Faculty and within the National Health Service utilising qualitative methods of enquiry. The evaluation study demonstrated that the use of the educational framework effectively educates faculty to construct and deliver simulation-based learning. Furthermore, the valuation demonstrated positive impacts on patient safety by increasing the confidence and skills of frontline staff and by improving the ‘preparedness’ of systems. It has also contributed to significant economic benefits within healthcare organisations.